A comparison of micro-scale projects undertaken by different agencies: the case for Perak Tengah / Ainun Mardiah Mohd Hanifah ... [et al.] - Mohd Hanifah, Ainun Mardiah; Mohd Sidek, Noor Zahirah; Mustaffa, Roslida (2006)
The research was undertaken to look at the micro scale projects by the residents in Perak Tengah with the involvement and assessment by the government and non government agencies such as Jabatan Pertanian, RISDA, FELCRA and PLB. The findings revealed that the choice of the micro scale projects were undertaken by the kampung people based on their interest but the training and advice provided by the agencies. Among the micro scale projects are food productions, goat and chicken cluster and many others . Even though there are problems faced by the participants, the p rojects had helped them to generate and increase their monthly income .It can be concluded that the helped given by the agencies is not sufficient enough in order to combat the hardcore poverty in the region. Many other persistent steps should be taken by those agencies in order to ensure the real successfulness of the projects . Further research is recommended in order to look at the involvement of other agencies and to cover many more respondents in these micro scale projects so that it will help the government to come out with the policies in order to achieve the objective of the poverty alleviation within the region .xiii